Filsafat Pendidikan Hadap-Masalah Paulo Freire dan Implikasinya terhadap Pendidikan Nasional - Siti Murtiningsih (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
Paulo Freire’s problem-posing education is an idea or a concept in which the development of students’ consciousness towards self-realities and their environments enables them to adopt critical and creative attitudes. The concept implies that teaching-learning process should emphasize a dialectical-emancipatory method and a curriculum involving students’ daily-life realities. While it bears a positive dimension of developing students' critical and creative thinking, the concept also has the negative dimension as it can be utopian. Nevertheless, problem-posing education is relevant to Indonesian education since it provides possible solutions to structural problems faced by Indonesian people.